A systems biology approach to studying the molecular mechanisms of osteoblastic differentiation under cytokine combination treatment - Hua Tan (Nature Portfolio, 2017)
Using computer simulations to optimize therapies Computer simulations using experimental data could optimize bone regeneration treatments. Xiaobo Zhou of Wake Forest University School of Medicine, Yunzhi Yang of Stanford University in the US and colleagues found that sequentially delivering two cell-signaling molecules to mouse bone marrow stromal cells (BMSCs), with four days in between, led to optimal growth of bone-forming cells in comparison to other delivery timings. They treated mouse BMSCs with ‘bone morphogenetic protein 2’ (BMP-2) and/or ‘insulin-like growth factor 1’ (IGF-1), which induce osteoblast differentiation and proliferation respectively. They then input the resultant microarray and proteomics data into a computer simulation model they constructed to study the cells’ behaviors over variable time scales and with varied biological processes. They found that delivering IGF-1 four days after BMP-2 was optimum for activating critical pathways for bone regeneration.